Ulwimi olunye alwanelanga tu (one language is never enough) : the role of language in consumer responses to sales slogans in the South African setting - Wright, Megan Anne (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.